ABOUT SURNAME “KAHN” AND ITS SPREADING - Sabirovich, Gaibov Bobir; Abdirazakovich, Khushbakov Hamidulla; Ziyadullayevich, Khujanov Nuriddin (International Journal of Psychosocial Rehabilitation, 2020)
The author has sought to elucidate the origins, content, significance, and distribution of the expression Kahn and its spreading in China, based on written sources and scholarly literature. The Sogdian word knδ – кан is most common in Christian, Monist, Buddhist texts found in East Turkestan. In the inscriptions of the Mughal mountain inscriptions, this word also means "city". This phrase, originally used as a part of toponyms (Samar + kand, Tosh + kent, Kohn + ibodom, Kan + duz, Kan + dahor, etc.), later spread to China through various invasions and trade relations, used for expression the meaning "samarkandian". The study emphasizes the use of this expression the person names, highlighting the importance of the Kahn’s name as an onomastic reference in the study of early medieval Sogd and Chinese history. In addition, the article analyzes the historical basis for the distribution of the Kahn name in China and the factors that influenced it. The author put forward a number of independent ideas about the use of this phrase in various sources and its connection with Samarkand.